Epidemiology and incidence of oral squamous cell carcinoma in the Iraqi population over 5 years (2014–2018). Issue 4 (11th April 2023) - Alshami, Muhanad L.; Al‐Maliky, Mohammed Abbood; Alsagban, Ali Arkan; Alshaeli, Ali J.
Abstract: Background: Oral squamous cell carcinoma is one of the most common and life‐threatening neoplasms worldwide, and is responsible for approximately 90% of all oral malignancies. Aim: This study was aimed at providing updated information on oral squamous cell carcinoma in all Iraqi governorates for the 5‐year period from 2014 to 2018, including the annual incidence and demographic variables. Materials and Methods: The total number of oral squamous cell carcinoma cases in Iraq, along with associated demographic information (age, sex, and site), for the 5‐year period from 2014 to 2018 was obtained. The statistical analysis consisted of descriptive analysis, including frequency, percentage, and mean ± standard deviation. A χ 2 test was performed to compare frequencies between male and female patients, among age groups, and among different OSCC sites. The χ 2 test was also used to assess the association of each OSCC site with age and sex. The significance threshold was set at p  < 0.05, and the confidence interval was set at 95%. The incidence rate of oral squamous cell carcinoma for each year was calculated by dividing the number of OSCC cases per year by the population of Iraq, then multiplying the result by 100, 000. Results: A total of 722 cases were recorded. Statistically, oral squamous cell carcinoma was found to be more prevalent in males and individuals over 40 years of age. The tongue was the most common site of occurrence. Lip squamous cell carcinoma cases were high in males. The incidence rate of oral squamous cell carcinoma was estimated to be 0.4 per 100, 000 people. Conclusion: Males and older people are at relatively higher risk of developing oral cancer. The tongue is the most affected site, but any site in the oral cavity may be involved. Further exploration of the causes of oral malignancy in Iraq is necessary to improve prevention strategies.